Archaeological Sources for the Study of Palestine: The Chalcolithic Period - Levy, Thomas E. (The Biblical archaeologist, 1986)
During the late fifth and fourth millennia B.C. significant technological and social changes occurred among societies living in Palestine. This paper, the first of a new series in BA, surveys the archaeological research that illuminates these changes.